Sustainable urban regeneration: the role of cultural heritage in Cultural Ecosystem Services (CES) - Soeiro, Diana (2022)
It is widely acknowledged that in the last few decades, culture has been playing an increasing role in urban regeneration. However, particularly in the realm of urban policy, the understanding of what culture is seems to be too narrow, often excluding vernacular culture. Why should vernacular culture be incorporated into urban policy and can it effectively contribute to the promotion of urban regeneration? Our case study is on Marvila and Beato (in Lisbon, Portugal), two parishes that share an industrial past and that were neglected in recent decades, but that are currently undergoing a regeneration process. Using the methodology proposed by Cultural Ecosystem Services (CES), we combine both qualitative and quantitative methodologies: a historical and observational approach and a questionnaire survey. Results show that not only tangible but also intangible heritage are key to designing an urban regeneration policy and this requires higher participation by the community and local actors.